Apakah yang Membuat Generasi Y Bahagia di Tempat Kerja? Studi Deskriptif dengan Tinjauan Sosiodemografis - Hidayati, Ira (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2024)
This study aims to identify factors that influence happiness at work in generation Y employees based on sociodemographic review. The research method applied is descriptive quantitative method using survey method by looking at the frequency of respondents' answers and cross-tabulating with several categories of response answers. The approach used in this research is indigenous psychology. The research sample consisted of 200 employees. Data collection was conducted through purposive sampling technique using questions in a questionnaire developed by Kim (2009) Center For Indege- nous & Cultural Psychology (CCIP) Faculty of Psychology UGM and modified by the author according to research needs. The results showed that there are five factors that make a person happy at work, namely (1) positive relationships with others (2) achievement at work (3) work environment both physical and non-physical (4) compensation (5) the work factor itself. The positive relationship factor with others occupies the largest percentage of the other four factors. Furthermore, the results of the analysis based on sociodemographic reviews show that there is no difference between marital status and factors that affect happiness at work. Furthermore, there is no difference between employment status and factors affecting happiness at work. Based on the last level of education, there are variations in the results obtained. Based on gender, there are differences in the dominant factors affecting happiness at work